Pelestarian dan Pemanfaatan Kawasan Kota Lama Sebagai Identitas Modern di Museum Al Wasliyah di Pasar Hindu, Medan - Ester Deatri Koestoro; Jelia Susan Sinaga; Marta Rebekka Tampubolon (Politeknik Pariwisata Medan, 2022)
The relief that appears is related to efforts to revive the old part of the city of Kesawan. Making it part of the former metropolis of Medan again as a meeting place for various ideas and uses that lead to preservation. Arrangement through the preparation of legal products (among other things Cultural Conservation) leads to a healthy situation for the preservation of various old buildings and environments. The utilization is related to ideological interests in order to utilize cultural identity which is closely related to educational functions. Likewise with academic interests, and not left behind are economic interests, including in relation to tourism